”Mawah” Profit Sharing System with Local Acehnese Wisdom Based on Islamic Perpective - Muhammad Ali; Mahadi Bahtera; Mustakim Sagita; Ayu Andira; Ziatul Via (Dinasti Research, 2024)
Aceh is an Indonesian province characterized by a predominantly Muslim population. Hence, the Islamic comprehension of economic principles, fairness, and profit-sharing systems has significant consequences for the economic progress of the Acehnese population. Research on the use of Islamic tenets in cattle farming companies may significantly benefit the welfare of the Acehnese people in this particular setting. Mawah is a commercial practice rooted in traditional conventions and local village knowledge. It involves verbal agreements between cattle owners and keepers for profit-sharing in cow husbandry. This research examines the